Results of clubfoot treatment after manipulation and casting using the Ponseti method: experience in Harare, Zimbabwe. Issue 10 (26th July 2016) - Smythe, Tracey; Chandramohan, Daniel; Bruce, Jane; Kuper, Hannah; Lavy, Christopher; Foster, Allen
Abstract: Objectives: The objective of this study was to evaluate the outcomes of the Ponseti manipulation and casting method for clubfoot in a tertiary hospital in Zimbabwe and explore predictors of these outcomes. Methods: A cohort study included children with idiopathic clubfoot managed from 2011 to 2013 at Parirenyatwa Hospital. Demographic data, clinical features and treatment outcomes were extracted from clinic records. The primary outcome measure was the final Pirani score (clubfoot severity measure) after manipulation and casting. Secondary outcomes included change in Pirani score (pre‐treatment to end of casting), number of casts for correction, proportion receiving tenotomy and proportion lost to follow up. Results: A total of 218 children (337 feet) were eligible for inclusion. The median age at treatment was 8 months; 173 children (268 feet) completed casting treatment within the study period. The mean length of time for corrective treatment was 10.2 weeks (9.5–10.9 weeks). Of the 45 children who did not complete treatment, 28 were under treatment and 17 were lost to follow up. A Pirani score of 1 or less was achieved in 85% of feet. Mean Pirani score at presentation was 3.80 (SD 1.15) and post‐treatment 0.80 (SD 0.56, P ‐value <0.0001). Severity of deformity and being male were associated with a higher (worse) final Pirani score. Severity and age over two were associated with an increase in the number of casts required to correct deformity. Conclusion: This case series demonstrates that the majority (80%+) of children with clubfoot can achieve a good outcome with the Ponseti manipulation and casting method.